The size of the expressed HIV reservoir predicts timing of viral rebound after treatment interruption. (28th January 2016) - Li, Jonathan Z.; Etemad, Behzad; Ahmed, Hayat; Aga, Evgenia; Bosch, Ronald J.; Mellors, John W.; Kuritzkes, Daniel R.; Lederman, Michael M.; Para, Michael; Gandhi, Rajesh T.
Abstract : Objectives: Therapies to achieve sustained antiretroviral therapy-free HIV remission will require validation in analytic treatment interruption (ATI) trials. Identifying biomarkers that predict time to viral rebound could accelerate the development of such therapeutics. Design: A pooled analysis of participants from six AIDS Clinical Trials Group ATI studies to identify predictors of viral rebound. Methods: Cell-associated DNA (CA-DNA) and CA-RNA were quantified in pre-ATI peripheral blood mononuclear cell samples, and residual plasma viremia was measured using the single-copy assay. Results: Participants who initiated antiretroviral therapy (ART) during acute/early HIV infection and those on a non-nucleoside reverse transcriptase inhibitor-containing regimen had significantly delayed viral rebound. Participants who initiated ART during acute/early infection had lower levels of pre-ATI CA-RNA (acute/early vs. chronic-treated: median <92 vs. 156 HIV-1 RNA copies/10 6 CD4 + cells, P  < 0.01). Higher pre-ATI CA-RNA levels were significantly associated with shorter time to viral rebound (⩽4 vs. 5–8 vs. >8 weeks: median 182 vs. 107 vs. <92 HIV-1 RNA copies/10 6 CD4 + cells, Kruskal–Wallis P  < 0.01). The proportion of participants with detectable plasma residual viremia prior to ATI was significantly higher among those with shorter time to viral rebound. Conclusion: Higher levels of HIV expression while on ART are associated with shorter time to HIV rebound after treatment interruption. Quantification of the active HIV reservoir may provide a biomarker of efficacy for therapies that aim to achieve ART-free HIV remission. Abstract : Supplemental Digital Content is available in the text